International transfer technology to India - Kumar, Muneesh (New Delhi, 1988)
This book is based on a comparative study of technology transfers to India from two important suppliers. It combines the theortical exposition of the subject, which is still some what obscure, with the practical orientation based on the first hand information obtained from corporate executives involved in import of technologies. The book may be very useful for corporate executives, policy makers and students concerned with import and absorption of technology.
Keywords: Technology and State